PENGARUH KEBIJAKAN PERPAJAKAN, KESADARAN WAJIB PAJAK, PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN, TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KPP PRATAMA SEBERANG ULU KOTA PALEMBANG: PENGARUH KEBIJAKAN PERPAJAKAN, KESADARAN WAJIB PAJAK, PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN, TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KPP PRATAMA SEBERANG ULU KOTA PALEMBANG - Masnoni (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
The purpose of this research is to find out whether Tax Policy, Awareness is Mandatory Taxes, Knowledge and Understanding of Taxation Influence Taxpayer Compliance MSMEs in Palembang City. The MSME taxpayers registered at the Pratama Seberang Ulu Tax Service Office (KPP) in Palembang City are the population that this study is focused on. Until a sample of 100 respondents was gathered, the sample selection in this study was conducted using a straightforward random procedure sampling. Primary data types were employed in this study. Primary data for this study came directly from original sources through documentation, which involved submitting a questionnaire to the source research, which in this case was MSME Taxpayers in Palembang City who were registered with the KPP. The study's findings demonstrate that tax policy has no bearing on taxpayer compliance, taxpayer awareness affects taxpayer compliance, and taxpayer knowledge and comprehension of taxes has no bearing on taxpayer compliance.